Virulence potential of antimicrobial-resistant extraintestinal pathogenic Escherichia coli from retail poultry meat in a Caenorhabditis elegans model - Chongwu Yang; Moussa S. Diarra; Muhammad Attiq Rehman; Linyan Li; Hai Yu; Xianhua Yin; Mueen Aslam; Catherine D. Carrillo; Chengbo Yang; Joshua Gong (Journal of Food Protection, 2023)
Healthy poultry can be a reservoir for extraintestinal pathogenic Escherichia coli (ExPEC), some of which could be multidrug resistant to antimicrobials. These ExPEC strains could contaminate the environment and/or food chain representing thus, food safety and human health risk. However, few studies have shown the virulence of poultry-source antimicrobial-resistant (AMR) ExPEC in humans. This study characterized AMR ExPEC and investigated the virulence potential of some of their isolates in a Caenorhabditis elegans infection model. A total of 46 E. coli isolates from poultry (chicken, n = 29; turkey, n = 12) retail meats and chicken feces (n = 4), or humans (n = 1) were sequenced and identified as ExPEC. Except eight, all remaining 38 ExPEC isolates were resistant to at least one antibiotic and carried corresponding antimicrobial resistance genes (ARGs). About 27 of the 46 ExPEC isolates were multidrug-resistant (≥3 antibiotic classes). Seven ExPEC isolates from chicken or turkey meats were of serotype O25:H4 and sequence type (ST) 131 which clustered with an isolate from a human urinary tract infection (UTI) case having the same serotype and ST. The C. elegans challenge model using eight of studied ExPEC isolates harboring various ARGs and virulence genes (VGs) showed that regardless of their ARG or VG numbers in tested poultry meat and feces, ExPEC significantly reduced the life span of the nematode (P < 0.05) similarly to a human UTI isolate. This study indicated the pathogenic potential of AMR ExPEC from retail poultry meat or feces, but more studies are warranted to establish their virulence in poultry and human. Furthermore, relationships between specific resistance profiles and/or VGs in these E. coli isolates for their pathogenicity deserve investigations.